Civil Society in Post-Euromaidan Ukraine : From Revolution to Consolidation - Shapovalova, Natalia; Burlyuk, Olga; Youngs, Richard (La Vergne : Ibidem Press, 2018)
This book is among the first comprehensive efforts to collectively and academically investigate the legacy of the Euromaidan in conflict-torn Ukraine within the domain of civil society broadly understood. The contributions to this book identify, describe, conceptualize, and explain various developments in Ukrainian civil society and its role in Ukraine's democratization, state-building, and conflict resolution by looking at specific understudied sectors and by tracing the situation before, during, and after the Euromaidan. In doing so, this trailblazing collection highlights a number of new themes, challenges, and opportunities related to Ukrainian civil society. They include volunteerism, grassroots community-based activism, social activism of churches, civic efforts of building peace and reconciliation, civic activism of journalists and digital activism, activism of think tanks, diaspora networks and the LGBT movement, challenges of civil society relations with the state, uncivil society, and the closing of civic space.
Organizing with Organizations: Factors that Contribute to the Sustainability of Internet-Based Civil Society InitiativesLeaders in Trust: The Churches' Social Activism in Post-Euromaidan Ukraine; Strategies to Fight Homophobia in Post-Euromaidan Ukraine: Constructing a Good Gay Citizen and Ukrainian Homonormative Patriotism; About the Authors.
Print version record.
eBooks on EBSCOhost
Keywords: Russo-Ukrainian War, 2014- -- Social aspects -- Ukraine; Civil society -- Ukraine; Ukraine -- History -- Revolution of Dignity, 2013-2014.; Ukraine -- Politics and government -- 1991-2014.; Guerre russo-ukrainienne, 2014- -- Aspect social -- Ukraine; Société civile -- Ukraine; Ukraine -- Histoire -- 2013-2014 (Révolution de la dignité); Ukraine -- Politique et gouvernement -- 1991-2014.; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; Civil society; Politics and government; Social aspects; Ukraine; Since 1991; History